The Storied World of James - Hearon, Holly E. (Interpretation, 2020)
This essay explores how third-person characters are employed in the letter of James to illustrate theological propositions. The words and actions of the characters are shown to shape social worlds in consequential ways and demonstrate the deeply relational nature of the letter’s theology. Using elements of narrative and socio-rhetorical criticisms, attention is given to setting, characterization, thematic development, and networks of signification. The essay demonstrates how storied episodes involving third-person characters contribute to the literary coherency of the letter and illustrate the inseparable relationship that binds humans and God with one another.